2021
DOI: 10.2519/jospt.2021.10340
|View full text |Cite
|
Sign up to set email alerts
|

Stuck in the Middle With You: Why a Broad-Brush Approach to Defining Central Sensitization Does Not Help Clinicians and Patients

Abstract: Synopsis Central sensitization is (1) increasingly interpreted as central nervous system hyperexcitability that accounts for a general increase in sensitivity, and (2) used to explain a variety of pain and nonpain symptoms. In this commentary, we argue that such a broad interpretation might not be clinically useful because it fails to distinguish one patient from another based on pathophysiological mechanisms and does not facilitate tailored treatment. We recommend that clinicians use a person-centered approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The discovery of CS was a major breakthrough in pain neuroscience as it demonstrated that there is no simple relationship between activity in peripheral nociceptors and pain. This realization is likely to have contributed to a change in attitudes of clinicians who would otherwise have diagnosed some patients with chronic pain as "malingerers, liars or hysterical [51]." The results from this study should clearly show biomedically-oriented clinicians that nearly one in five patients attending outpatient PT for a common musculoskeletal disorder present with CS.…”
Section: Discussionmentioning
confidence: 77%
“…The discovery of CS was a major breakthrough in pain neuroscience as it demonstrated that there is no simple relationship between activity in peripheral nociceptors and pain. This realization is likely to have contributed to a change in attitudes of clinicians who would otherwise have diagnosed some patients with chronic pain as "malingerers, liars or hysterical [51]." The results from this study should clearly show biomedically-oriented clinicians that nearly one in five patients attending outpatient PT for a common musculoskeletal disorder present with CS.…”
Section: Discussionmentioning
confidence: 77%
“…A large proportion of patients with TMDm are more sensitive than healthy controls to a variety of experimental noxious stimuli 5–8 . However, the sensitivity to experimental noxious stimuli of patients with TMDm is not found to be globally enhanced, so a detailed evaluation of the somatosensory system is needed to better understand the pathophysiological mechanisms 5–9 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] However, the sensitivity to experimental noxious stimuli of patients with TMDm is not found to be globally enhanced, so a detailed evaluation of the somatosensory system is needed to better understand the pathophysiological mechanisms. [5][6][7][8][9] The somatosensory profiles of patients with TMDm can be assessed through quantitative sensory testing. 8,10 Quantitative sensory testing is a psychophysical testing approach assessing the subjective responses to quantified and controlled stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Cayrol et al suggested that pain should be evaluated based on the factors impacting pain or daily activities [ 18 ]. Physicians may focus on behaviors such as fear of movement, passive coping strategies, and muscle activity or movement patterns that cause pain [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the bio-psycho-social nature of chronic musculoskeletal pain, it seems that the educational approach based on the bio-psycho-social model is an appropriate educational model for treating these people [16,17]. Cayrol et al suggested that pain should be evaluated based on the factors impacting pain or daily activities [18]. Physicians may focus on behaviors such as fear of movement, passive coping strategies, and muscle activity or movement patterns that cause pain [18].…”
Section: Introductionmentioning
confidence: 99%